Consumer and Functional Properties of Amur Grape Vitis amurensis Rupr. as a Raw Material for Food Enrichment - Aleksey Aleshkov; Anna Zhebo (Journal of Global Innovations in Agricultural Sciences, 2025)
The Amur grape (Vitis amurensis Rupr.) is a wild grape species rich in bioactive compounds, including polyphenols, resveratrol, and iron, making it a potential functional ingredient for food fortification. Despite its proven antioxidant and nutritional benefits, its application in meat product fortification remains unexplored. The present study aims to evaluate the potential use of the Amur grape to fortify mass consumption food products. A systematic review of relevant literature was conducted using the PRISMA algorithm, analyzing sources from Scopus, Web of Science, and Science Direct. Findings indicate that Amur grape extracts exhibit significant antioxidant activity (367.24±0.53 mg ascorbic acid equivalents/g), which can extend the shelf life of meat products and enhance their nutritional profile. Hence, they exhibit anti-anemic and antioxidant effects when added to food products. The polyphenols of Amur grapes, primarily resveratrol, enhance the antioxidant effect of ascorbic acid and exhibit anticarcinogenic, cardioprotective, anti-stressor, and other effects. The fortification of food products with compositions from Amur grape also improves their organoleptic characteristics and extends shelf life due to high antioxidant activity. The conclusion indicates that there are relatively few developments in food product technologies with Amur grapes, and mass consumption food products, including meat products, fortified with Amur grapes are practically nonexistent on the market. The findings contribute to the development of natural, clean-label antioxidant solutions, aligning with consumer trends toward healthier, functional foods. Keywords: Amur grape, Vitis amurensis, functional food ingredient, resveratrol, meat products, antioxidant properties, natural food additives, food preservation.